Manajemen Strategi dan Implementasi Manajemen Penerimaan Peserta Didik Baru di SMK Ma'arif Cijulang - Andi Abdul Hanafi; Imron Rosadi; Irsyad Khoerul Imam; Rini Indah Sari; Ulpah Nupusiah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to describe the Strategic Management of New Student Admissions at SMK MA'ARIF CIJULANG, new students are a very important activity in school. It is said so because if there is no acceptance, the school will not get students. If this happens, theexistence of the schoolwill be disrupted. This research was conducted using descriptive qualitative methods using datacollection methods in the form of: interviews, observationand documentation. The results showed that (1) the strategic management activities of new student admissions at SMK MA'ARIF Cijulang were carried out in PPDB SMK MA'ARIF Cijulang. The promotion displayed the excellence and quality of the school, namely evidence of student achievement in trophies, certificates, medals, etc. (2) Planning before PPDB is by determining the capacity of prospective new students, determining the requirements for accepting new prospective students, then preparing PPDB informationmedia and finally preparing administration and facilities and infrastructure. (2) The implementation of PPDB begins with the formation of a committee and the division of tasks for each committee. After that formed the admissions selection team, determination of the selection time, PPDB selection and the last is the announcement of the selection results. (3) The results of the acceptance of new students at SMK MA'ARIF CIJULANG arequite good, this is evidenced in the acceptance period in the 2022/2023 school year SMK MA'ARIF CIJULANG obtained as many as 19 students within a period of two months. (4) Evaluation of PPDB at SMK MA'ARIF CIJULANG using the accountability report system (LPJ )after PPDB. This report was submitted in aspecial committee meeting regarding the process of PPDB activities from beginning to end.